A robust fatigue parameter determination method for a local fatigue cohesive zone model. (June 2023) - Leciñana, I.; Zurbitu, J.; Renart, J.; Turon, A.
Graphical abstract: Highlights: A parameter determination method for a fatigue cohesive zone model is developed. The parameter determination method is based on experimental fatigue fracture data. The method enables modelling both fatigue onset and propagation. The model was validated through a 3D benchmark with non-self-similar crack growth. The method has the potential to be used for predictive and virtual testing purposes. Abstract: In this work, a robust method for determining the input fatigue parameters of a fatigue cohesive zone model recently developed by Dávila is presented. The method is based on surrogate modelling and multi objective optimization. Experimental data from delamination tests is used for the parameter determination, highlighting the phenomenological nature of the model. The ability to simulate both fatigue onset and propagation is verified for two different monotonic cohesive laws. The predictive capability of the methodology is validated against the experimental results of a partially reinforced double cantilever beam specimen (R-DCB) with non-self-similar crack propagation.